Introduction: Adolescence and Social Deviance - Torrente, Ginesa; Vazsonyi, Alexander T. (Anales de Psicología / Annals of Psychology, 2012)
The goal of the present monograph is to bring together recent scholarship from teams of researchers across different developmental contexts to study predictors and correlates of adolescent maladjustment or deviance. These include intrapersonal factors, such as the Big Five personality construct, but also interpersonal factors, including family processes and relationships, and peer group relations. They also include larger structural characteristics, such as socioeconomic status or consequences of migratory processes, now prevalent and relevant across societies